Biodegradable Polymers in Clinical Use and Clinical Development - Domb, A. J. (Abraham J.), editor of compilation; Jain, Jay Prakash (Hoboken, NJ : Wiley, 2011)
'This book focuses on biodegradable polymers that are already in clinical use or under clinical development. Synthetic and natural polymers will be included. This excludes polymers that have been investigated and did not reach clinical development. The purpose of this book is to provide updated status of the polymers that are clinical use and those that are now being developed for clinical use and hopefully will reach the clinic during the next 5 years. The book provides information that of interest to academics and practicing researchers including chemists, biologists and bioengineers and users: physicians, pharmacists'--
'This book will focus on biodegradable polymers that are already in clinical use or under clinical development'--
Keywords: Biodegradable plastics; Polumers in medicine